A long afterglow material based on MOF template method and its preparation method and application

The long afterglow material prepared by the MOF template method solves the problems of fast attenuation of fluorescence intensity and uneven particle size of existing materials, achieving higher fluorescence brightness and afterglow duration, which is suitable for surgical navigation.

CN116478687BActive Publication Date: 2025-02-18NANKAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211538531.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-02-18
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

The existing long afterglow materials have problems such as fast fluorescence intensity decay, large particle size and unevenness, and poor water environment stability in surgical navigation, which cannot meet the requirements of surgical navigation.

Method used

Long afterglow materials are prepared by MOF template method, and the MOF with a determined metal ion ratio is formed by coordination between porphyrin derivatives and metal ions, which improves the spatial regularity of metal ions and increases lattice defects, thereby improving the fluorescence brightness and afterglow of the material. Duration.

Benefits of technology

The prepared long afterglow material has higher fluorescence brightness and afterglow duration, with an average particle size between 10-1000nm, and has good water stability, making it suitable for surgical navigation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116478687B_ABST
    Figure CN116478687B_ABST
Patent Text Reader

Abstract

The present invention discloses a long afterglow material based on the MOF template method, and a preparation method and application thereof. The preparation method of the present invention comprises the following steps: (1) preparing a MOF template: uniformly mixing a porphyrin derivative and a metal source in a solvent, and obtaining a MOF template through a hydrothermal reaction; (2) preparing a precursor: dispersing the MOF template obtained in step (1) in the solvent again, adding a chromium source, mixing for a period of time, separating to obtain a precipitate, and freeze-drying to obtain the precursor; (3) subjecting the precursor obtained in step (2) to high-temperature treatment in an air atmosphere to obtain the long afterglow material. The present invention uses MOF as a precursor, which can well arrange the spatial distribution and element ratio of metal ions, thereby obtaining a long afterglow material with a more regular crystal form and a more uniform element distribution during the calcination process, which is beneficial to the formation of lattice defects inside the system, thereby improving the brightness of the afterglow material and the duration of the afterglow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nanomaterials, and in particular to a long afterglow material based on a MOF template method, and a preparation method and application thereof. Background Art

[0002] The surgical treatment process of tumors includes preoperative tumor localization, intraoperative lesion resection, and postoperative effect evaluation. Surgical navigation helps to determine the boundaries of tumor tissue and discover tiny tumors (metastases) during surgery, minimizing future troubles. The tumor imaging detection equipment currently used in clinical practice, such as magnetic resonance imaging (MRI) and CT, is large and has a low signal-to-noise ratio, and cannot be used for intraoperative imaging navigation. At present, the operation is mainly based on the doctor's experience and judgment, and there are often regrets that the boundary determination is not accurate enough and the tiny lesions are not completely removed. Therefore, if real-time imaging navigation with a high signal-to-noise ratio can be achieved during surgery, it will be of great significance to improve the accuracy of tumor resection.

[0003] Long afterglow material is a material that can be excited by ultraviolet or visible light and can continue to emit light (afterglow) for several hours after the light source is removed for a period of time. Since it does not require an external light source (relying on afterglow) during the luminescence process, it will not cause autofluorescence of biological tissues and can improve the imaging signal-to-noise ratio. Therefore, it has been used by researchers for biological imaging research in recent years, but there are no reports of its clinical use. The afterglow generated by the material can be easily detected and collected using a CCD camera, which greatly reduces the operating cost, realizes real-time imaging during surgery, and improves the guiding role of imaging for surgery. The current problem that needs to be solved is to increase the afterglow duration and luminescence intensity of the material.

[0004] Researchers in my country have done a lot of valuable work on the use of long afterglow materials for in vivo imaging or detection. Although the fluorescence brightness and afterglow duration of long afterglow materials have increased, most materials still have the problem of rapid fluorescence intensity decay (generally the fluorescence brightness decreases by at least one order of magnitude after 30 minutes), and the fluorescence signal intensity recovered after secondary excitation is limited. In order to obtain sufficient signal intensity, the injection dose must be increased, which also brings potential safety risks. These long afterglow materials cannot currently meet the requirements for surgical navigation.

[0005] From this point of view, how to use structural design to reduce the particle size of inorganic long afterglow materials while having excellent luminescence properties and improving their aqueous phase stability is the key to obtaining long afterglow surgical navigation materials.

[0006] Although inorganic long afterglow materials have incomparable potential advantages in surgical navigation, they face two major contradictions in their application: 1. The long afterglow materials prepared by existing methods have excellent fluorescence brightness and afterglow duration, but the particle size is large (tens of microns) and uneven. Reducing the particle size will inevitably lose the number of traps and electrons in the matrix, and also reduce the depth of the traps, which reduces the fluorescence intensity and afterglow duration. 2. The stability in the water environment is poor, and surgical navigation cannot be achieved by intravenous injection. Summary of the invention

[0007] The present invention provides a method for preparing a long afterglow material, the preparation method comprising the following steps:

[0008] (1) Preparing a MOF template: mixing a porphyrin derivative and a metal source in a solvent, and then subjecting the mixture to a hydrothermal reaction to obtain a MOF template;

[0009] (2) Preparing a precursor: dispersing the MOF template obtained in step (1) in the solvent again, adding a chromium source, mixing for a period of time, separating to obtain a precipitate, and freeze-drying to obtain the precursor;

[0010] (3) Under air atmosphere, subjecting the precursor obtained in step (2) to high temperature treatment to obtain the long afterglow material.

[0011] According to an embodiment of the present invention, the porphyrin derivatives are selected from porphyrin derivatives containing amino or carboxyl groups. Exemplarily, the porphyrin derivatives are selected from tetracarboxylic acid phenylporphyrin (TCPP), tetraaminophenylporphyrin (TAPP), hematoporphyrin monomethyl ether (HMME), dihydrochlorin e6 (Ce6). In the present invention, porphyrin derivatives and metal ions (such as zinc ions and gallium ions) are selected to coordinate to form a MOF with a determined metal ion ratio, so that the metal ions are assembled according to a certain ratio and spatial position, and the spatial regularity of the metal ions is improved, thereby increasing the possibility of forming lattice defects during the calcination process, increasing the number of defects, and ultimately improving the afterglow brightness and time of the afterglow material.

[0012] According to an embodiment of the present invention, in step (1), the molar ratio of the porphyrin derivative to the metal source is (0.05-0.07):(0.1-0.6), for example, 0.05:0.2, 0.05:0.3, 0.05:0.4, 0.05:0.5, 0.07:0.2, 0.07:0.3, 0.07:0.4, 0.07:0.5, 0.06:0.1, 0.06:0.2, 0.06:0.3, 0.06:0.4, 0.06:0.5, 0.06:0.6.

[0013] Preferably, the metal source is selected from at least one of metal nitrates, acetates, chlorides and sulfates. Preferably, the metal is at least one of zinc, gallium and germanium, preferably zinc and gallium.

[0014] Exemplarily, the metal source comprises Zn(OAc) 2 and Ga(NO 3 ) 3 , Zn(OAc) 2 and Ga(NO 3 ) 3 The molar ratio is 0.1-0.3:0.2-0.3.

[0015] According to an embodiment of the present invention, in step (1), the solvent is selected from water, such as deionized water. The amount of the solvent used in the present invention is not specifically limited, as long as the porphyrin derivative and the metal source can be dissolved. Exemplarily, the amount of the solvent used is 10-20 mL.

[0016] According to an embodiment of the present invention, in step (1), the mixing is performed at room temperature.

[0017] According to an embodiment of the present invention, in step (1), the conditions for uniform mixing can be selected by methods known in the art, such as vigorous stirring for 3 hours.

[0018] According to an embodiment of the present invention, in step (1), the hydrothermal method is carried out in a reaction kettle known in the art.

[0019] According to an embodiment of the present invention, in step (1), the conditions of the hydrothermal method include: reacting at 150-200° C. for 10-24 hours, for example, reacting at 180° C. for 10-24 hours.

[0020] According to an embodiment of the present invention, in step (1), the MOF template needs to be further washed and / or dried. Preferably, the washing and drying can be performed by methods known in the art. Preferably, the washing is performed by washing with the solvent and a volatile organic solvent. Furthermore, the drying is, for example, drying at 50-80°C.

[0021] According to an embodiment of the present invention, in step (1), the MOF template is a solid, for example, a dark brown solid. Exemplarily, when the metal source comprises Zn(OAc) 2 and Ga(NO 3 ) 3 In the obtained MOF template, Ga reacts with the functional groups outside the porphyrin derivatives, while Zn is chelated inside the porphyrin ring of the porphyrin derivatives.

[0022] According to an embodiment of the present invention, in step (2), the chromium source is selected from chromium compounds, such as chromium nitrate.

[0023] According to an embodiment of the present invention, in step (2), the mass ratio of the chromium source to the MOF template is (0.000288-0.00864): 1

[0024] According to an embodiment of the present invention, in step (2), the mixing can be performed by methods known in the art, such as stirring at room temperature for 1 hour.

[0025] According to an embodiment of the present invention, in step (2), the freeze-drying conditions are freeze-drying at 0°C to -50°C for 1-48 hours, for example, freeze-drying at -50°C for 24 hours.

[0026] According to an embodiment of the present invention, in step (3), the conditions for high temperature treatment include: reacting at 800° C.-1000° C. for 1-10 hours, for example, reacting at 900° C. for 4 hours.

[0027] According to an embodiment of the present invention, in step (3), the long afterglow material is a solid powder, preferably a white solid powder.

[0028] The present invention also provides a long afterglow material, which is prepared by the above preparation method.

[0029] According to an embodiment of the present invention, the long afterglow material comprises Cr 3+ Doped zinc gallate, denoted as ZnGa 2 O 4 :Cr 3 + .

[0030] According to an embodiment of the present invention, in the long afterglow material, Cr 3+ The doping amount is greater than 0.001%, preferably not greater than 1%, for example, 0.1%-0.6%, and for example, 0.5%.

[0031] According to an embodiment of the present invention, the average particle size of the long afterglow material is 10-1000 nm, for example, 170 nm.

[0032] According to an embodiment of the present invention, the long afterglow material has a regular crystal form. Preferably, the long afterglow material is a 111 crystal form with a crystal lattice of 0.48 nm.

[0033] According to an embodiment of the present invention, the signal-to-noise ratio of the long afterglow material is 541 after being irradiated at 254 nm for 10 minutes.

[0034] According to an embodiment of the present invention, the long afterglow material is water stable.

[0035] The present invention also provides application of the long afterglow material in the field of biological imaging.

[0036] Beneficial Effects

[0037] The present invention uses MOF as a precursor, which can well arrange the spatial distribution and element ratio of metal ions, so as to obtain a long afterglow material with more regular crystal form and more uniform element distribution during the calcination process, which is beneficial to the formation of lattice defects (traps) inside the system, thereby improving the brightness of the afterglow material and the duration of the afterglow.

[0038] The present invention utilizes a removable polymer template and selects a porphyrin derivative to prepare the MOF, which can achieve precise control of the ratio and spatial position of metal elements in the template. For example, Ga reacts with the functional groups outside the porphyrin derivative, while Zn is chelated inside the porphyrin ring of the porphyrin derivative, inducing the inorganic long afterglow material to grow according to the template size, and the expected nanoparticles can be obtained; the reduction in the number of electrons, trap concentration and depth in the crystal caused by the reduction in particle size can be compensated, thereby effectively improving the fluorescence brightness and duration of the material. Finally, a nano long afterglow material with high purity and excellent performance is obtained, providing accurate navigation for the field of biological imaging (such as tumor resection). BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the preparation process of the long afterglow material of the present invention;

[0040] Figure 2 This is the morphology characterization result of ZGC-1 prepared in Example 1.

[0041] Figure 3 This is the afterglow performance test result of ZGC-1 prepared in Example 1.

[0042] Figure 4 This is the afterglow stability performance test result of ZGC-1 prepared in Example 1.

[0043] Figure 5 The results of the evaluation in living animals of Application Example 1 are shown. DETAILED DESCRIPTION

[0044] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0045] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0046] In the following embodiments, the porphyrin derivatives are selected from tetracarboxylic acid phenylporphyrin (TCPP), tetraaminophenylporphyrin (TAPP), hematoporphyrin monomethyl ether (HMME), and dihydrochlorin e6 (Ce6).

[0047] Example 1

[0048] The preparation steps of long afterglow materials are as follows:

[0049] 1. Synthesis of Zn-Ga-TMOF (ZGT)

[0050] Weigh 0.06 mmol of tetracarboxylic acid phenylporphyrin (TCPP), 0.2 mmol of Zn(OAc) 2 , 0.2 mmol of Ga(NO 3 ) 3 , dissolved in 20 mL of deionized water, stirred vigorously at room temperature for 6 hours. Then transferred to a 45 mL polytetrafluoroethylene reactor and reacted at 180 ° C for 18 hours. Cooled to room temperature to obtain a black-brown solid. Washed with deionized water and ethanol 3 times, dried in an oven at 60 ° C, and obtained 20 mg of ZGT-1 solid powder.

[0051] 2. Synthesis of Zn-Ga-TMOF-Cr (ZGTC)

[0052] The ZGT-1 obtained in step 1 was redispersed in 10 mL of deionized water, and 200 uL of Cr(NO 3 ) 3 solution (2 mg / mL) into the system, ZGT-1 and Gr(NO 3 ) 3 The mass ratio of 1:0.02 was 1:0.02, and the mixture was stirred at room temperature for 1 hour. The precipitate was separated by centrifugation, washed with deionized water for 3 times, and freeze-dried to obtain 20 mg of dark brown ZGTC-1.

[0053] 3. Preparation of ZGC-1 nanoparticles

[0054] The dark brown ZGTC-1 obtained in step 2 was placed in a tube furnace and reacted at 900°C for 4 hours in an air atmosphere. It was then naturally cooled to room temperature to obtain a white ZGC-1 solid powder with a yield of 40%. It was found from the test that the Cr doping amount in the ZGC-1 prepared in Example 1 was 0.5%.

[0055] Test Example 1

[0056] 1. Morphological characterization of ZGC-1

[0057] like Figure 2As shown in Figures ae and b, the ZGC-1 prepared in Example 1 exhibits a regular rod-like structure, and the hydrated particle size is about 170 nm. Figure 2 As shown in middle f, high-resolution TEM confirms that the ZGC-1 material has high crystallinity and its lattice is 0.48nm, which is consistent with the 111 crystal form of ZGC.

[0058] 2. Characterization of afterglow performance of ZGC-1

[0059] The ZGC-1 obtained in Example 1 was dissolved in water to obtain a ZGC-1 suspension (3 mg / mL), and a ZGC-1 sample in water was obtained. After irradiating the ZGC-1 sample in water and the solid ZGC-1 sample with a 254 nm ultraviolet lamp for 10 minutes, the ultraviolet lamp was turned off and the afterglow intensity within 60 minutes was recorded. The afterglow intensity of the sample was recorded using an IVIS imaging system and an afterglow decay curve was plotted.

[0060] like Figure 3 As shown, the afterglow performance of ZGC-1 obtained in Example 1 remains high even in water. The afterglow intensity of ZGC-1 in water decreases by about 22% compared with the initial value, but still remains at a high level. Although the afterglow intensity of ZGC-1 in water decreases rapidly in the early stage, the decay rate in the later stage is basically the same as that of solid ZGC-1. It can be calculated that the average life of ZGC-1 in water is extended by τ avg The average lifetime of ZGC-1 solid is extended to 192 seconds. avg It is 216s, indicating that water has little effect on the afterglow lifetime of the prepared ZGC.

[0061] like Figure 4 As shown in (a), solid ZGC-1 exhibits good repeatability and photostability, with no obvious signal decay within three excitation cycles.

[0062] 3. Characterization of the afterglow stability of ZGC-1

[0063] The test conditions for afterglow stability are basically the same as those for the above-mentioned afterglow performance characterization, specifically as follows: Take the ZGC-1 solid powder obtained in Example 1 to obtain a ZGC-1 sample in water. After irradiating the solid ZGC-1 sample with a 5000lm light-emitting diode for 10 minutes, turn off the LED and record the afterglow intensity within 5 minutes, which is recorded as one cycle. Repeat the above process 4 times and record the afterglow intensity of four excitation cycles. The afterglow intensity of the sample is recorded using the IVIS imaging system and the afterglow decay curve is plotted.

[0064] The NIR PL of ZGC-1 powder can be restored to the initial afterglow within at least four cycles of irradiation with a 5,000lm LED, with no obvious fluctuations, such as Figure 4 As shown in (b), the ZGC-1 powder has good excitation repeatability. The high afterglow stability of ZGC-1 can greatly extend the imaging time and is sufficient for in vivo bioimaging and molecular fluorescence-guided surgery.

[0065] Example 2

[0066] The preparation steps of this embodiment are basically the same as those of embodiment 1, except that:

[0067] In step 1, tetracarboxylic acid phenylporphyrin (TCPP) is replaced by tetraaminophenylporphyrin (TAPP), TAPP, Zn(OAc) 2 and Ga(NO 3 ) 3 The molar ratio is the same as that in Example 1, and 20 mg of ZGT-2 solid powder is obtained;

[0068] In step 2, ZGT-1 was replaced by ZGT-2, and ZGT-2 and Gr(NO 3 ) 3 The mass ratio is the same as that in Example 1; lyophilization is performed to obtain 20 mg ZGTC-2;

[0069] In step 3, ZGTC-2 was placed in a tube furnace and reacted at 900° C. for 4 hours in an air atmosphere, and then naturally cooled to room temperature to obtain a white ZGC-2 solid powder with a yield of 35%.

[0070] The test shows that the Cr doping amount in the ZGC-1 prepared in Example 2 is 0.5%.

[0071] Example 3

[0072] The preparation steps of this embodiment are basically the same as those of embodiment 1, except that:

[0073] In step 1, tetracarboxylic acid phenylporphyrin (TCPP) is replaced by hematoporphyrin monoethyl ether (HMME), HMME, Zn(OAc) 2 and Ga(NO 3 ) 3 The molar ratio is the same as that in Example 1, and 20 mg of ZGT-3 solid powder is obtained;

[0074] In step 2, ZGT-1 was replaced by ZGT-3, and ZGT-3 and Gr(NO 3 ) 3 The mass ratio is the same as that in Example 1; lyophilization is performed to obtain 20 mg ZGTC-3;

[0075] In step 3, ZGTC-3 was placed in a tube furnace and reacted at 900° C. for 4 hours in an air atmosphere, and then naturally cooled to room temperature to obtain a white ZGC-3 solid powder with a yield of 40%.

[0076] The test shows that the Cr doping amount in the ZGC-1 prepared in Example 3 is 0.5%.

[0077] Example 4

[0078] The preparation steps of this embodiment are basically the same as those of embodiment 1, except that:

[0079] In step 1, tetracarboxylic acid phenylporphyrin (TCPP) is replaced by dihydrochlorin e6 (Ce6), Ce6, Zn(OAc) 2 and Ga(NO 3 ) 3 The molar ratio is the same as that in Example 1, and 20 mg of ZGT-4 solid powder is obtained;

[0080] In step 2, ZGT-1 was replaced by ZGT-4, which was then combined with Gr(NO 3 ) 3 The mass ratio is the same as that in Example 1; lyophilization is performed to obtain 20 mg ZGTC-4;

[0081] In step 3, ZGTC-4 was placed in a tube furnace and reacted at 900° C. for 4 hours in an air atmosphere, and then naturally cooled to room temperature to obtain a white ZGC-4 solid powder with a yield of 40%.

[0082] The test shows that the Cr doping amount in the ZGC-1 prepared in Example 4 is 0.5%.

[0083] Application Example 1

[0084] 24-hour afterglow decay experiment and mouse imaging experiment

[0085] After irradiating the solid ZGC-1 sample with 254nm UV light for 10min, the UV light was turned off and the PL photos were captured using the IVIS imaging system within 24 hours. In the absence of any external illumination, the charge-coupled device (CCD) camera still clearly detected the NIR PL after 24 hours. After 24 hours, the signal-to-noise ratio (SNR) dropped from the initial 2,567 to 541.

[0086] The PL characteristics of the ZGC prepared in Example 1 were also evaluated in living animals. The ZGC suspension (3 mg / mL) was excited with a UV lamp (254 nm, 6 W) for 10 minutes and then injected subcutaneously into mice. High luminescence was still observed 5 minutes after injection, and the SNR was 134 at this time.

[0087] The above results confirm that the long afterglow materials (PLNPs) prepared using MOF templates as precursors have the potential for application in bioimaging.

[0088] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a long afterglow material, characterized in that: The preparation method comprises the following steps: (1) Preparing a MOF template: mixing a porphyrin derivative and a metal source in a solvent, and then subjecting the mixture to a hydrothermal reaction to obtain a MOF template; the porphyrin derivative is selected from a porphyrin derivative containing an amino group or a carboxyl group; the molar ratio of the porphyrin derivative to the metal source is (0.05-0.07):(0.1-0.6); the conditions of the hydrothermal reaction include: reacting at 150-200°C for 10-24 hours; the metal source includes Zn(OAc)2 and Ga(NO3)3, and the molar ratio of Zn(OAc)2 to Ga(NO3)3 is 0.1-0.3:0.2-0.3; (2) Preparing a precursor: dispersing the MOF template obtained in step (1) in the solvent again, adding a chromium source, mixing for a period of time, separating a precipitate, and freeze-drying to obtain the precursor; the mass ratio of the chromium source to the MOF template is (0.000288-0.00864):1; (3) Under air atmosphere, subjecting the precursor obtained in step (2) to high temperature treatment to obtain the long afterglow material; In the long afterglow material, Cr 3+ The doping amount is greater than 0.001% and not greater than 1%; the average particle size of the long afterglow material is 10-1000nm; the long afterglow material has water stability and a regular crystal form; The porphyrin derivative is selected from at least one of tetracarboxylic acid phenylporphyrin, tetraaminophenylporphyrin, hematoporphyrin monomethyl ether, and dihydrochlorin e6.

2. The preparation method according to claim 1, characterized in that: The metal source is selected from at least one of metal nitrates, acetates, chlorides and sulfates; the metal is at least one of zinc, gallium and germanium.

3. The preparation method according to claim 1, characterized in that: In step (1), the solvent is selected from water; In step (1), the MOF template needs to be further washed and / or dried.

4. The preparation method according to claim 1, characterized in that: In step (2), the chromium source is selected from chromium compounds; In step (2), the freeze-drying conditions are freeze-drying at 0°C to -50°C for 1-48 hours.

5. The preparation method according to claim 1, characterized in that: In step (3), the high temperature treatment conditions include: reacting at 800°C-1000°C for 1-10 hours; In step (3), the long afterglow material is solid powder.

6. A long afterglow material, characterized in that: The long afterglow material is prepared by the preparation method according to any one of claims 1 to 5.

7. The long afterglow material according to claim 6, characterized in that: The long afterglow material includes Cr 3+ Doped zinc gallate, denoted as ZnGa2O4:Cr 3+ .

8. The long afterglow material according to claim 6 or 7, characterized in that: In the long afterglow material, Cr 3+ The doping amount is greater than 0.001% and not greater than 1%; The average particle size of the long afterglow material is 10-1000nm; The long afterglow material has a regular crystal form; After the long afterglow material was irradiated at 254 nm for 10 min, its signal-to-noise ratio was 541; The long afterglow material is water stable.

9. The long afterglow material according to claim 8, characterized in that: The average particle size of the long afterglow material is 10-170 nm.

Citation Information

Patent Citations

  • Long-afterglow nanomaterial prepared by using template method

    CN112442364A